The effect of career anchors, job-esteem, and work engagement on retention intention in hospital nurses - Miran, Kim; Ji-Ah, Song (Edelweiss Applied Science and Technology, 2024)
This descriptive study aimed to analyze the effect of career anchors, job esteem, and work engagement on retention intention among hospital nurses while identifying factors contributing to retention intention in this group. The study involved 174 nurses with over six months of clinical experience employed at three general hospitals. The dominant career anchor among hospital nurses was security/stability (4.59), followed by life-style (4.52), technical/functional competence (4.13), and service/dedication (4.12). Hospital nurses’ retention intention was predicted by the entrepreneurial creativity (β=0.289, p<.001), job-esteem (β=0.268, p<.001), and job engagement (β=-0.295, p<.001) of career anchors. These factors collectively accounted for 35.2% of the variance (F=10.360, p<.001). Conclusion: In the future, we aim to conduct studies analyzing factors influencing retention intention and extract trends based on career anchor types and sample groups. This will inform detailed career development and personnel management policies.